Comic Media in Learning Fable Stories for Second Grade Elementary School Students - Ni Putu Yunita Chandra Dewi; Ni Nyoman Ganing; Maria Goreti Rini Kristiantari (Indonesian Journal Of Educational Research and Review, 2022)
The students' low interest in reading and the lack of students' understanding of reading without pictures led to the need for developing comics as a medium of learning. The purpose of this research is to create comic media in the learning of fable stories for second-grade elementary school students. The type of research used is development research. This development study utilizes the ADDIE model, which consists of Analysis, Design. Development, Implementation, and Evaluation. The research subjects consisted of 1 learning media expert and 1 learning design expert. The test subjects included 2 teachers and 1 student. The methods used in collecting data are observation and questionnaires. The instrument used in collecting data is a questionnaire. The technique used to analyze the data is descriptive quantitative. The result of the research is that the material expert test got a percentage of 86.00% in the very good category with very decent information. The trial of learning media design experts at a percentage of 90.00% with a very decent description and very good category. The teacher's response to the use of media is 89.00%, and the students are 90.40%, with both categories very good. It is concluded that the comics developed are suitable for use in second-grade elementary school students and can increase students' reading interest.